The Worker in Video Game Industry: The gap between indie and incorporated video game developers in Indonesia - Maulana Akbar; Indri Juwita Asmara (Journal of Games, Game Art, and Gamification, 2022)
The Indonesian video game industry is gaining good momentum as the national video game market continues to grow. However, the contribution of local video game developers is still very minimal. This study will look at the composition of local video games from the point of view of their human resources, from two entities that often appear, namely incorporated and indie. The results of this study indicate that the striking difference between the two entities is in the utilization of human resources from their educational background. While the most common is the habit of using outsourced labor.